Queen Garnet plum juice and raspberry cordial in mildly hypertensive obese or overweight subjects: A randomized, double-blind study - Bhaswant, Maharshi; Brown, Lindsay; Mathai, Michael L. (Journal of functional foods, 2019)
[Display omitted] •A randomized, double-blinded, placebo-controlled trial, involving 29 human volunteers with BMI >25 Kg/m2 along with high-normal or mild-hypertension.•Participants were requested to drink 250 ml of either Queen Garnet plum juice or raspberry cordial drink every morning.•Queen Garnet plum juice, which is a rich source of anthocyanins, decreased blood pressure, fasting plasma insulin, glucose, leptin and inflammatory cytokines.•This study suggests that daily consumption of QG could attenuate the development of cardiovascular and metabolic diseases. The anthocyanin, cyanidin 3-glucoside, in Queen Garnet (QG) plums reduced cardiovascular parameters, obesity and inflammation in diet-induced metabolic syndrome in rats. We have now assessed whether QG juice improves cardiovascular and metabolic risk factors and markers of inflammation in mildly hypertensive overweight or obese humans. The 32 subjects were randomly divided into two groups consuming either QG juice or Placebo (raspberry cordial) drinks for 12 weeks. QG juice decreased systolic blood pressure by 12 ± 3 mmHg, diastolic blood pressure by 9 ± 2 mmHg, insulin by 6 ± 3 pmol/L, and leptin by 4 ± 2.5 ng/ml, and increased adiponectin by 3.62 ± 0.28 µg/ml. Cyanidin 3-glucoside is the likely active component of the plum juice, with possible additive effects of other flavonoids such as quercetin glycosides. Thus, QG juice decreased blood pressure and attenuated some risk factors of metabolic syndrome after 12 weeks suggesting that daily consumption could attenuate the development of cardiovascular and metabolic diseases.